Why muscle strengthening exercises should target the quadriceps and gluteus maximus in patients with knee osteoarthritis?: Effects of knee pain on muscle volume and fatty degeneration based on AI-assisted cross-sectional analysis - Do Kyung Lee; Hyeon Su Kim; Kyung Rae Ko; Jong Pil Yoon; Jun-Il Yoo (Journal of Orthopaedic Translation, 2025)
Background: Sarcopenia, characterized by age-related muscle loss, traditionally presents as systemic muscle atrophy. However, knee osteoarthritis (OA) patients often exhibit localized quadriceps muscle atrophy, suggesting a potential pain-related mechanism distinct from classical sarcopenia. This study aimed to investigate the relationship between knee OA pain and selective muscle atrophy, particularly focusing on its role as a potential aggravating factor for sarcopenia. Methods: Eighty-nine patients scheduled for unilateral primary total knee arthroplasty were analyzed. Preoperative computed tomography was used to compare muscle volume and intramuscular adipose tissue (IMAT) proportion between the more painful limb (Group 1) and the contralateral, less painful limb (Group 2). Analysis included both compartmental evaluation (anterior, medial, and posterior thigh compartments; hip abductors and external rotators) and individual muscle assessment. Results: Group 1 demonstrated significant volume reduction in the anterior thigh compartment (specifically vastus lateralis, intermedius, and medialis) and gluteus maximus, compared to Group 2 (p < 0.05). IMAT proportion was significantly higher in most muscles of Group 1, except for hip abductors, tensor fascia latae, and gluteus minimus (p < 0.05), suggesting widespread fatty degeneration despite selective volume loss. Conclusion: Knee osteoarthritis–related pain induces selective atrophy in the anterior thigh compartment and gluteus maximus while promoting diffuse fatty infiltration throughout the lower extremity. These findings suggest that OA-associated pain may exacerbate sarcopenia by driving both region-specific muscle loss and widespread intramuscular adipose degeneration. The translational potential of this article: These findings underscore the importance of pain control as a primary therapeutic goal in patients with knee osteoarthritis. They also highlight the clinical necessity of targeted strengthening of the quadriceps and gluteus maximus muscles, given the role of knee pain in inducing secondary, selective muscle atrophy. Furthermore, symptoms commonly observed in elderly patients with OA—such as limping, giving way, lower extremity weakness, and patellofemoral knee pain—may not be attributable solely to the aging process. Rather, they may reflect secondary muscular adaptations driven by chronic pain during the progression of osteoarthritis (Figure 1).